The Relationship between Self Efficacy and Job Satisfaction in Disabled Workers at PT. Maspion 1 - Trisnasari Dyta (Proceedings of The ICECRS, 2020)
This study aims to test empirically whether there is a relationship between self efficacy and job satisfaction in disabled workers at PT. Maspion Unit 1 Sidoarjo. Self efficacy in question is a motivator in the individual about the beliefs owned to organize and display the actions needed to succeed in completing tasks owned by workers with disabilities. Self-efficacy has a close relationship with work processes in employees. Based on the work process carried out by workers with disabilities owned self-efficacy will have an impact on job satisfaction both related to themselves and with the company.This research was conducted on disabled workers in PT. Maspion Unit 1 Sidoarjo as many as 56 people, consisting of 23 female subjects and 33 male subjects. Based on the age of the research subjects categorized from the age of 33 years - 54 years. And based on the work period of research subjects ranging from 13 years to 16 years of work. Data collection tool in the form of a Likert scale questionnaire, which consists of two measuring devices, namely a self efficacy measuring device consisting of 30 items and a job satisfaction measurement consisting of 54 items. Based on the analysis of research data, the correlation between self-efficacy and job satisfaction among workers with disabilities is 0.005 and p is 0.371; correlation between self efficacy and job satisfaction in disabled workers. This shows that there is a significant correlation between self efficacy and job satisfaction among disabled workers at PT. Maspion Unit 1 Sidoarjo.